A toughened ceramic material and an additive manufacturing method thereof
By adding zirconia and nanospherical zirconium aluminum alloy to the alumina ceramic materials and using a variety of photocuring adhesives of different molecular weights, the problem of poor toughness of alumina ceramic materials is solved, and its mechanical properties and sintering density are significantly improved.
Patent Information
- Application Number
- CN202411493658.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Due to its ionic bond characteristics and large grain structure, alumina ceramic materials have poor fracture toughness and are difficult to meet certain high-demand mechanical properties.
By adding zirconia and nanospherical zirconium aluminum alloy to the alumina ceramic material and using a variety of photocuring adhesives of different molecular weights, the sintering rate and the internal stress are improved, and the mechanical properties of the ceramic material are improved.
It significantly improves the hardness, toughness, bending strength and sintering density of ceramic materials, reduces porosity, and improves the material's resistance to deformation and cracking.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of additive manufacturing of ceramics, and in particular to a toughened ceramic material and an additive manufacturing method thereof. Background Art
[0002] Ceramic additive manufacturing technology, as an advanced material processing method, builds ceramic structures of complex shapes by layer-by-layer additive molding, overcoming many limitations in traditional ceramic molding technology. In the current mainstream ceramic additive manufacturing technology, ceramic particles with a photocurable binder are laid on a molding platform to form a ceramic particle layer (usually micrometer to millimeter thick), and then heated, reacted with moisture in the surrounding environment, or laid on a molding platform, and irradiated with electromagnetic radiation with a suitable wavelength (such as ultraviolet light, visible light) to induce the curing, i.e., solidification, of the binder. The entire layer or only selected areas of the layer are cured to form a raw (unfired) ceramic material layer. Subsequently, another layer of ceramic particles is deposited on the previous layer of raw ceramic, the new layer is selectively cured, and the layer-by-layer process is repeated until the desired structure of the raw ceramic material is obtained. Finally, the raw ceramic material is partially fired to achieve degreasing and removal of the binder, and then sintered to obtain the final ceramic material.
[0003] Alumina is a commonly used ceramic particle for additive manufacturing, which has the advantages of high hardness, low dielectric constant, good high temperature stability and corrosion resistance. However, due to the ionic bond characteristics and large grain structure of alumina ceramic materials, it has the problem of poor fracture toughness. Summary of the invention
[0004] In order to improve the problem of poor toughness of alumina ceramic materials produced by additive manufacturing of alumina, the present application provides a toughened ceramic material and an additive manufacturing method thereof.
[0005] In a first aspect, the present application provides a toughened ceramic material, the raw materials of which include: ceramic particles, a surface modifier, and a photocuring adhesive; the ceramic particles include aluminum oxide, zirconium oxide, and nano-spherical zirconium aluminum alloy in a mass ratio of 50 to 70:15 to 25:3 to 10.
[0006] Preferably, the median particle size of the aluminum oxide is 10 to 50 μm, the median particle size of the zirconium oxide is 3 to 15 μm, and the median particle size of the nano-spherical zirconium-aluminum alloy is 10 to 50 nm.
[0007] Preferably, the zirconium content of the nano-spherical zirconium-aluminum alloy is 25-35wt%, and the average aspect ratio of the nano-spherical zirconium-aluminum alloy is less than 1.5.
[0008] Zirconia can achieve toughening of ceramic materials through grain refinement, microcrack toughening, phase transformation toughening, crack redirection and bifurcation, etc. However, it should be recognized that alumina and zirconia have different thermal expansion coefficients. During the sintering and cooling process, this difference will cause internal stress in the ceramic material, resulting in deformation and cracking risks, and reducing the mechanical strength of the material.
[0009] The addition of nano-spherical zirconium-aluminum alloy can alleviate the thermal stress caused by the difference in thermal expansion coefficient between alumina and zirconia to a certain extent. The reason may be: First, the nano-zirconium-aluminum alloy can adjust its sintering rate, so that the two ceramic substrates will not shrink rapidly and inconsistently during cooling due to different expansion coefficients, and alleviate the thermal stress caused by the difference in thermal expansion coefficient between alumina and zirconia to a certain extent. Second, the thermal expansion coefficient of zirconium-aluminum alloy may be between that of alumina and zirconia, which can be used as a sintering aid to reduce the sintering temperature of ceramics, promote the densification of ceramic powders during sintering, reduce the formation of pores and defects, and thus improve the sintering density and density of ceramics. Third, zirconium-aluminum alloy can be used as a heterogeneous nucleating agent to promote the refinement of alumina and zirconia grains. Refined grains help to improve the mechanical properties and deformation cracking resistance of ceramics. Fourth, the addition of nano-spherical zirconium-aluminum alloy can improve the interface characteristics and compatibility between alumina and zirconia, enhance the interface contact between the two, and thus improve the mechanical properties of ceramic materials.
[0010] In addition, the nano-spherical zirconium-aluminum alloy has good fluidity and permeability due to its shape and size, and can be effectively dispersed between the gaps between alumina and zirconium oxide, giving full play to its good effect of reducing internal stress during sintering and cooling.
[0011] The aspect ratio described in this application refers to the ratio between the two longest radial lengths of the powder particles, more specifically the ratio of the longer diameter to the shorter diameter. Its average value can be obtained by calculating the arithmetic mean of a typical sample of particles. In addition, the median particle size is the D50 particle size.
[0012] Preferably, the photocurable adhesive comprises acrylic resin A and acrylic resin B in a mass ratio of 1:0.95-1.35; the molecular weight of the acrylic resin A is 9000-30000, and the molecular weight of the acrylic resin B is 50000-80000.
[0013] The molecular weight of the acrylic resin described in the present application refers to the number average molecular weight; in the free radical copolymerization of the acrylic resin, the methods for regulating the molecular weight include but are not limited to adding a chain transfer agent, a molecular weight regulator, lowering the reaction temperature, controlling the monomer concentration, changing the feeding method, etc.
[0014] Preferably, the acrylic resin A and acrylic resin B are acrylic resins that can be cured under light irradiation with a wavelength of 365-405 nm.
[0015] Preferably, the photocurable adhesive further comprises polyol poly(meth)acrylate, and the amount of the polyol poly(meth)acrylate is 5-10% of the mass of the acrylic resin A.
[0016] Preferably, the polyol poly (meth) acrylate is selected from one or more of ethylene glycol di (meth) acrylate, glycerol poly (meth) acrylate, trimethylolpropane tri (meth) acrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, trimethylolpropane di (meth) acrylate, trimethylolpropane acrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol tetraacrylate, and pentaerythritol tetramethacrylate.
[0017] In the process of high-temperature degreasing to remove the adhesive, a single adhesive will decompose and volatilize rapidly, easily producing a large amount of gas. These gases cannot escape quickly, and will form pores in the ceramic structure, resulting in increased porosity, reduced density and mechanical strength. In addition, the mismatch between the decomposition rate of the adhesive and the sintering rate of the ceramic powder may cause thermal stress, causing structural damage such as deformation or cracking. To solve this problem, the present application uses a variety of adhesives with different molecular weights in order to alleviate the pore problem caused by the rapid and large-scale decomposition of the adhesive, and to make the decomposition rate of the adhesive more compatible with the sintering rate of the material, thereby reducing internal stress.
[0018] It should be noted that acrylic resin A and acrylic resin B cannot effectively penetrate into the gaps of the nano-spherical zirconium-aluminum alloy due to their molecular weight, resulting in more pores between the ceramic materials. These pores are prone to form microcracks after sintering, which is not conducive to improving the mechanical strength of the ceramic material. The present application adopts a low molecular weight resin monomer polyol poly (meth) acrylate, which can not only improve its permeability, reduce porosity, and improve the mechanical properties of the ceramic material, but also its multi-functional group structure makes the small molecule resin monomer have a higher photoreactivity and an outstanding photocuring effect.
[0019] Preferably, the mass ratio of the ceramic particles, the surface modifier and the photocurable adhesive is 100:2-5:120-200.
[0020] Preferably, the surface modifier is selected from one or more of oleic acid, stearic acid, ammonium polyacrylate, and silane coupling agent.
[0021] Preferably, the surface modifier further comprises sorbitol, and the sorbitol accounts for 5 to 10 wt % of the total amount of the surface modifier.
[0022] The flexible straight-chain structure of sorbitol gives it good permeability. At the same time, the large amount of alcohol hydroxyl groups it contains can effectively promote the penetration and surface modification of other components in the surface modifier into ceramic particles, especially the penetration of nano-spherical zirconium-aluminum alloy, which inhibits agglomeration and promotes dispersion.
[0023] In a second aspect, the present application provides an additive manufacturing method for toughened ceramic materials, which uses any of the above-mentioned raw material ratios of the ceramic materials and performs operations including the following steps:
[0024] Alumina, zirconium oxide, nano-spherical zirconium-aluminum alloy, a surface modifier and ethanol are uniformly mixed, a light-curing adhesive is added, and the mixture is uniformly mixed again to obtain ceramic powder;
[0025] Laying a ceramic powder layer on the platform of the photocuring molding equipment, and then inducing the photocuring binder in the ceramic powder layer to cure by light irradiation to obtain a green ceramic layer; repeating this step until a green ceramic body with a desired structure is obtained;
[0026] The raw ceramic body is dried at a temperature of 40-80°C to remove moisture; then the temperature is raised to 400-600°C at a rate of 3-5°C / min, and the body is kept warm for degreasing for 4-6 hours to remove the binder; then the body is cooled to room temperature, and finally the body is sintered at 1300-1650°C.
[0027] During the degreasing stage, the present application controls the temperature rise rate so that the temperature is raised to the degreasing temperature at a uniform rate. The compounding selection of the above-mentioned photocuring adhesive can be combined to adjust the sequential decomposition of different photocuring adhesives to prevent the generation of a large number of pores in the ceramic structure, which helps to improve the mechanical strength of the resulting ceramic material.
[0028] In summary, this application has the following beneficial effects:
[0029] This application uses zirconium oxide to toughen and strengthen alumina ceramics, and uses nano-spherical zirconium-aluminum alloy to adjust the sintering rate of zirconium oxide and alumina, thereby alleviating the problem of inconsistent expansion coefficients between the two, which easily causes shrinkage deformation and cracking. At the same time, it can refine the grains of ceramic materials, improve their sintering density, and ensure the anti-deformation and cracking performance and mechanical properties of ceramic materials.
[0030] The present application adopts three photocuring adhesives with different molecular weights. On the one hand, it can alleviate the problem of too fast decomposition of photocuring adhesives during ceramic sintering to produce a large number of unexpected pores, and thermal stress caused by the mismatch between the decomposition rate of photocuring adhesives and the sintering rate; on the other hand, it effectively improves the problem of poor bonding of current conventional adhesives to nano-spherical zirconium aluminum alloys, thereby ensuring the mechanical properties of ceramic materials. DETAILED DESCRIPTION
[0031] Example
[0032] Embodiment 1, a toughened ceramic material is prepared by an additive manufacturing method, and the specific steps are as follows:
[0033] Take 600g of alumina (median particle size 30μm), 180g of zirconium oxide (median particle size 10μm) and 50g of nano-spherical zirconium-aluminum alloy (median particle size 30nm, zirconium content 30wt%, average aspect ratio 1.3), 1500g of a mixed solution of KH-560 and ethanol (KH-560 content 3.5wt%), and stir evenly; then add 580g of acrylic resin A (molecular weight 18000), 700g of acrylic resin B (molecular weight 60000), and 55g of trimethylolpropane tri(meth)acrylate, stir evenly, and obtain ceramic powder for use.
[0034] A ceramic powder layer is laid on the platform of the photocuring molding equipment, and then the ceramic powder layer is irradiated with light with a wavelength of 400nm to cure the photocurable adhesive to obtain a green ceramic layer with a thickness of 100μm; this step is repeated twice to obtain a green ceramic body with three green ceramic layers.
[0035] The raw ceramic body is dried at 60°C for 6 hours to remove moisture; then the temperature is increased to 500°C at a rate of 4°C / min, and the body is kept warm for degreasing for 5 hours to remove the binder, and then the body is cooled in air to room temperature; the degreased body is then placed in a sintering furnace, the temperature is increased to 1600°C at a rate of 10°C / min, and the body is kept warm for 3 hours, and the toughened ceramic material is obtained by cooling in the furnace.
[0036] Embodiment 2, a toughened ceramic material is prepared by an additive manufacturing method, and the specific steps are as follows:
[0037] Take 550g of aluminum oxide (median particle size 20μm), 150g of zirconium oxide (median particle size 5μm) and 40g of nano-spherical zirconium aluminum alloy (median particle size 20nm, zirconium content 28wt%, average aspect ratio 1.1), 1600g of a mixed solution of oleic acid and ethanol (oleic acid content 3wt%), and stir evenly; then add 460g of acrylic resin A (molecular weight 20000), 490g of acrylic resin B (molecular weight 50000), 40g of trimethylolpropane tri(methyl)acrylate, stir evenly, and obtain ceramic powder for use.
[0038] A ceramic powder layer is laid on the platform of the photocuring molding equipment, and then the ceramic powder layer is irradiated with light with a wavelength of 400nm to cure the photocurable adhesive to obtain a green ceramic layer with a thickness of 100μm; this step is repeated twice to obtain a green ceramic body with three green ceramic layers.
[0039] The raw ceramic body is dried at 50°C for 8 hours to remove moisture; then the temperature is increased to 600°C at a rate of 5°C / min, and degreased for 4 hours to remove the binder, and then cooled to room temperature in air; the degreased body is then placed in a sintering furnace, heated to 1600°C at a rate of 10°C / min, sintered for 3 hours, and cooled in the furnace to obtain a toughened ceramic material.
[0040] Embodiment 3, a toughened ceramic material is prepared by an additive manufacturing method, and the specific steps are as follows:
[0041] Take 650g of alumina (median particle size 30μm), 230g of zirconium oxide (median particle size 10μm) and 70g of nano-spherical zirconium aluminum alloy (median particle size 25nm, zirconium content 30wt%, average aspect ratio 1.3), 2100g of a mixed solution of KH-560 and ethanol (KH-570 content 4.5wt%), and stir evenly; then add 800g of acrylic resin A (molecular weight 30000), 1000g of acrylic resin B (molecular weight 80000), and 75g of trimethylethylene glycol di(methyl)acrylate, stir evenly, and obtain ceramic powder for use.
[0042] A ceramic powder layer is laid on the platform of the photocuring molding equipment, and then the ceramic powder layer is irradiated with light with a wavelength of 380nm to cure the photocurable adhesive to obtain a green ceramic layer with a thickness of 100μm; this step is repeated twice to obtain a green ceramic body with three green ceramic layers.
[0043] The raw ceramic body is dried at 80°C for 5 hours to remove moisture; then the temperature is increased to 450°C at a rate of 3°C / min, and the body is kept warm for degreasing for 5 hours to remove the binder, and then the body is cooled in air to room temperature; the degreased body is then placed in a sintering furnace, the temperature is increased to 1450°C at a rate of 15°C / min, and the body is kept warm for 3.5 hours, and the toughened ceramic material is obtained by cooling in the furnace.
[0044] Example 4, a toughened ceramic material, differs from Example 1 in that the raw materials for preparing the ceramic powder are different, specifically: 1500g of a mixed solution of KH-560 and ethanol (KH-560 content 3.5wt%) is replaced by a mixed solution of 1500g KH-560, sorbitol and ethanol (KH-560 content 3.2wt%, sorbitol content 0.3wt%).
[0045] Example 5 is a toughened ceramic material. The difference from Example 1 is that trimethylolpropane tri(meth)acrylate is replaced by an equal amount of acrylic resin A (molecular weight 18000).
[0046] Example 6, a toughened ceramic material, is different from Example 1 in that acrylic resin B (molecular weight 60,000) is replaced by an equal amount of acrylic resin A (molecular weight 18,000).
[0047] Example 7, a toughened ceramic material, is different from Example 1 in that acrylic resin A (molecular weight 18,000) is replaced by an equal amount of acrylic resin B (molecular weight 60,000).
[0048] Example 8, a toughened ceramic material, is different from Example 1 in that acrylic resin A (molecular weight 18,000) and trimethylolpropane tri(meth)acrylate are replaced by an equal amount of acrylic resin B (molecular weight 60,000).
[0049] Comparative Example
[0050] Comparative Example 1 is a toughened ceramic material, which differs from Example 8 in that the nano-spherical zirconium aluminum alloy (median particle size of 30 nm, zirconium content of 30 wt%, average aspect ratio of 1.3) is replaced by an equal amount of zirconium oxide (median particle size of 10 μm).
[0051] Comparative Example 2 is a toughened ceramic material, which differs from Example 8 in that an equal amount of aluminum oxide (with a median particle size of 30 μm) is used to replace zirconium oxide (with a median particle size of 10 μm).
[0052] Performance testing
[0053] 1. Vickers hardness and fracture toughness: Use a Vickers hardness tester to measure the sample. Specifically, press a regular tetrahedral diamond indenter into the sample surface at a set pressure, hold for 10 seconds, and then remove the pressure. A certain shape of indentation will be formed on the sample surface. Then, by measuring the diagonal length of the indentation on the surface of the sample, the surface area of the indentation is obtained. The ratio of the pressure to the indentation surface area is the Vickers hardness. For each sample, measure the hardness values of ten points, and take the average value to get the Vickers hardness value of the sample (H v ).
[0054] In addition, the crack length after pressure application was measured by an optical microscope equipped with a Vickers hardness tester, and the fracture toughness (K IC ).
[0055]
[0056] Where: P represents the loading load (5 Kg), N; F represents the indentation area, mm 2 ; E represents Young's modulus of ceramic material, GPa; Hv represents Vickers hardness, GPa; c represents crack half length, mm; d1, d2 represent indentation length, mm; holding time is 10s.
[0057] 2. Bending strength: The three-point bending strength test method was used to test the test samples using a universal material testing machine. The sample span was set to 30 mm and the loading speed was 1 mm / min. Each sample was tested 5 times. The calculation formula for the bending strength is shown below.
[0058]
[0059] Wherein, σ is the bending strength, MPa; F is the maximum load that the sample can withstand, N; B is the cross-sectional width of the sample, mm; h is the cross-sectional height of the sample, mm; L is the test span, mm.
[0060] 3. Porosity: The test was performed using AutoPore IV 9500 fully automatic mercury intrusion porosimeter.
[0061] Table 1. Performance test results
[0062] Sample Project Vickers hardness / GPa <![CDATA[Fracture toughness / MPa·m 1 / 2 > Bending strength / MPa Porosity / % Example 1 15.6 6.3 1035 37.1 Example 2 13.9 7.0 970 39.5 Example 3 17.1 6.5 1160 35.7 Example 4 16.8 7.1 1110 36.1 Example 5 13.4 5.6 905 40.4 Example 6 14.2 5.5 970 39.6 Example 7 13.9 5.9 950 39.2 Example 8 12.3 5.4 905 43.3 Comparative Example 1 9.5 3.8 735 45.3 Comparative Example 2 8.2 3.1 670 45.8
[0063] Test result analysis:
[0064] 1. Combining Examples 1 to 8 and Comparative Examples 1 to 2 and Table 1, it can be seen that toughening alumina ceramics with zirconium oxide and nano zirconium-aluminum alloy powder can significantly improve the mechanical properties of ceramic materials such as hardness, toughness, and bending strength, and reduce its porosity. And adding zirconium oxide and nano zirconium-aluminum alloy to alumina alone cannot achieve the best effect. The main reason may be that nano zirconium-aluminum alloy can adjust the sintering rate of ceramic powder and alleviate the inconsistency of thermal expansion rates between alumina and zirconium oxide, thereby improving the deformation and cracking problem caused by the ceramic material during the heating and cooling process, and effectively ensuring the mechanical properties of the ceramic material after sintering.
[0065] In addition, nano-zirconium-aluminum alloy has the function of refining ceramic grains, improving sintering density, enhancing compatibility and interface bonding, and can also effectively reduce ceramic structural defects and improve its mechanical properties.
[0066] 2. Combining Example 1 and Examples 5 to 8 with Table 1, it can be seen that the use of a photocurable adhesive compounded with a variety of macromolecular resins and small molecular resin monomers can effectively improve the mechanical properties of ceramic materials. The reason may be that using a variety of resins or resin monomers as a photocurable adhesive can adjust the decomposition rate of the adhesive during the sintering process, reduce the unexpected pores caused by the rapid decomposition of the adhesive, and suppress the problem of thermal stress caused by the mismatch between the decomposition rate of the adhesive and the sintering rate; thereby improving the mechanical properties of the ceramic material.
[0067] In addition, small molecule resin monomers (polyol poly (meth) acrylates) can improve the poor flow of large molecule photocuring adhesives and the poor permeability of tiny gaps between ceramic powders. They also improve the poor bonding of ceramic powders, especially nano-spherical zirconium-aluminum alloys, thereby improving the mechanical properties of ceramic materials.
[0068] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A toughened ceramic material, characterized in that: In parts by mass, the raw materials of the ceramic material include: ceramic particles, a surface modifier, and a photocurable adhesive; the ceramic particles include aluminum oxide, zirconium oxide, and nano-spherical zirconium-aluminum alloy in a mass ratio of 50-70:15-25:3-10; the zirconium content of the nano-spherical zirconium-aluminum alloy is 15-25wt%, and the average aspect ratio of the nano-spherical zirconium-aluminum alloy is less than 1.5; the photocurable adhesive includes acrylic resin A, acrylic resin B, and polyol poly (meth) acrylate in a mass ratio of 1:0.95-1.35:0.05-0.1; the molecular weight of the acrylic resin A is 9000-30000, and the molecular weight of the acrylic resin B is 50000-80000.
2. The ceramic material according to claim 1, characterized in that The median particle size of the aluminum oxide is 10 to 50 μm, the median particle size of the zirconium oxide is 3 to 15 μm, and the median particle size of the nano-spherical zirconium-aluminum alloy is 10 to 50 nm.
3. The ceramic material according to claim 1, characterized in that The polyol poly(meth)acrylate is selected from one or more of ethylene glycol di(meth)acrylate, glycerol poly(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane triacrylate, trimethylol glycol di(meth)acrylate, trimethylolpropane acrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol tetraacrylate, and pentaerythritol tetramethacrylate.
4. The ceramic material according to claim 1, characterized in that The surface modifier includes one or more of oleic acid, stearic acid, ammonium polyacrylate, and silane coupling agent.
5. The ceramic material according to claim 4, characterized in that The surface modifier further comprises sorbitol, and the sorbitol accounts for 5-10 wt % of the total amount of the surface modifier.
6. A method for additive manufacturing of toughened ceramic materials, characterized in that: Using the raw material ratio of the ceramic material according to any one of claims 1 to 5, and performing the following steps: Alumina, zirconium oxide, nano-spherical zirconium-aluminum alloy, a surface modifier and ethanol are uniformly mixed, a light-curing adhesive is added, and the mixture is uniformly mixed again to obtain ceramic powder; Laying a ceramic powder layer on the platform of the photocuring molding equipment, and then inducing the photocuring binder in the ceramic powder layer to cure by light irradiation to obtain a green ceramic layer; repeating this step until a green ceramic body with a desired structure is obtained; The raw ceramic body is dried at a temperature of 40-80°C to remove moisture; then the temperature is raised to 400-600°C at a rate of 3-5°C / min, and the body is kept warm for degreasing for 4-6 hours to remove the binder; then the body is cooled to room temperature, and finally the body is sintered at 1300-1650°C.
Citation Information
Patent Citations
Photocuring 3D printing alumina-based ceramic material as well as preparation method and application thereof
CN115991595A
Preparation method of high-toughness aluminum oxide sheet
CN116283243A